Economic values of environmental services of three forest areas in South Ogan Komering Ulu District, South Sumatra, Indonesia - ENDA KARTIKA SARI; ANDY MULYANA; MIRZA ANTONI; DESSY ADRIANI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sari EK, Mulyana A, Antoni M, Adriani D. 2022. Economic values of environmental services of three forest areas in South Ogan Komering Ulu District, South Sumatra, Indonesia. Biodiversitas 23: 6180-6190. Forest provides environmental services in the form of provisioning, regulating, supporting and cultural services. However, forest is often valued from its timber products, neglecting its broader role in delivering environmental services especially its role in maintaining ecological functions. Forests in South Ogan Komering Ulu District, South Sumatra, Indonesia have high ecological importance in delivering environmental services, yet these forests are pressured by clearing and conversion into plantations and agriculture. The study aimed to comprehensively calculate the total economic value of environmental services delivered by three forest areas in South Ogan Komering Ulu, namely Gunung Raya Wildlife Reserve, Saka Production Forest and Saka Limited Production Forest. We calculated total economic value by incorporating the use value, which consists of direct use value and indirect use value, and the non-use value, which consists of option value, existence value and bequest value. The results revealed that the total economic value of the three forest areas is IDR 863,868,883,037. In more detail, the use value consisted of direct use value with IDR 354,378,792,460 contributing to 41.02% and indirect use value with IDR 509,309,370,324 contributing to 58.96% to the total economic value. The non-use value is from the option value, the existence value and bequest value with IDR 97,449,120 (0.01%), IDR 65,512,153 (0.01%) and IDR 17,758,980 (0.0021), respectively. Our study implies that forest has tremendous ecological functions which provide a very high economic value and environmental services, where these functions are often neglected.